Analisis Respon Pasar Modal Terhadap Puncak Kasus Covid-19 Fase 1 dan 2 di Indonesia - I Bagus Ngurah Alit Putra Wiryawan; I Komang Sumerta (Jurnal Riset Akuntansi dan Keuangan, 2023)
The COVID-19 pandemic has evoked a capital market response that has raised concerns among investors and economic analysts. Shareholders in the capital market are more likely to secure their money in companies that are strong against the impact of the pandemic. The peak of positive confirmation cases in Indonesia has also affect the condition of capital market investors. The peak of this case also had an impact on conditions on the Indonesia Stock Exchange (IDX) during trading because investors reacted to the information on the handling of this COVID-19 case. This investor reaction can be measured by the variables of Abnormal Return (AR) and Trading Volume Activity (TVA). This study aims to examine the market response from information on peak case events, especially stock prices and trading volume on the stock exchange. This research used an event study approach. The sample of this research was companies listed on the Indonesia Stock Exchange (IDX) and listed on the LQ45 index in 2021. The historical data used stock price and trading volume data from the second day before (T-2) the peak of phase 1 and 2 COVID-19 cases in Indonesia until the second day after the peak (T+2). Based on the analysis, it can be obtained that: (1) there was no significant difference in the abnormal return of the LQ45 stock in phase 1 and phase 2 of the peak of COVID-19 cases in Indonesia, and (2) there was a significant difference in cumulative abnormal returns of LQ45 shares in phase 1 and phase 2 of the peak of COVID-19 cases in Indonesia, and (3) there was a significant difference in the trading volume of LQ45 stock activity in phase 1 and phase 2 of the peak of COVID-19 cases in Indonesia.